2009
DOI: 10.1371/journal.pone.0004888
|View full text |Cite
|
Sign up to set email alerts
|

Adult-Young Ratio, a Major Factor Regulating Social Behaviour of Young: A Horse Study

Abstract: BackgroundAdults play an important role in regulating the social behaviour of young individuals. However, a few pioneer studies suggest that, more than the mere presence of adults, their proportions in social groups affect the social development of young. Here, we hypothesized that aggression rates and social cohesion were correlated to adult-young ratios. Our biological model was naturally-formed groups of Przewalski horses, Equus f. przewalskii, varying in composition.Methodology/Principal FindingsWe investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 33 publications
2
34
0
1
Order By: Relevance
“…West et al, 2003), appear therefore to play a crucial role in order for the young to develop the typical low level/low rate of aggression typical of natural social groups. In a study performed on natural family bands of Przewalski horses, Bourjade et al (2009a) found that the overall rate of aggression towards peers in 1 and 2 year old horses was negatively correlated with the adult-young ratio. When this ratio was low (less adults present), the young horses showed more aggressiveness, more segregation from adults and more bonding with same age partners.…”
Section: Development Of Social Skillsmentioning
confidence: 98%
See 4 more Smart Citations
“…West et al, 2003), appear therefore to play a crucial role in order for the young to develop the typical low level/low rate of aggression typical of natural social groups. In a study performed on natural family bands of Przewalski horses, Bourjade et al (2009a) found that the overall rate of aggression towards peers in 1 and 2 year old horses was negatively correlated with the adult-young ratio. When this ratio was low (less adults present), the young horses showed more aggressiveness, more segregation from adults and more bonding with same age partners.…”
Section: Development Of Social Skillsmentioning
confidence: 98%
“…Berger, 1977;Bourjade et al, 2009a;Feh, 1999;Salter and Hudson, 1982). Finally, family bands may group temporarily with other bands, especially in winter when risks of predation may increase.…”
Section: Stable Group Compositionmentioning
confidence: 99%
See 3 more Smart Citations